Alienation in Main Character Guy in The Free Guy Movie (2021) - Hilwa Aulia Luthfiah; Muhammad Rayhan Bustam (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
This study examines the alienation experienced by the character Guy in the film Free Guy. This study employs Karl Marx’s theory of alienation. Karl Marx’s theory identifies four main aspects of alienation: alienation from the product of labor, alienation from the labor process, alienation from fellow human beings, and alienation from oneself. This study also employs a descriptive qualitative research method. This method was chosen because the study aims to describe the aspects of alienation as they occur, based on the data without any manipulation. Consequently, the study concludes that the alienation depicted in this film encompasses three aspects: alienation from the product of labor, alienation from the labor process, and alienation from oneself. Keywords: Alienation, Free Guy, Karl Marx